Uncertainties of simulated aerosol optical properties induced by assumptions on aerosol physical and chemical properties: An AQMEII-2 perspective. (August 2015) - Curci, G.; Hogrefe, C.; Bianconi, R.; Im, U.; Balzarini, A.; Baró, R.; Brunner, D.; Forkel, R.; Giordano, L.; Hirtl, M.; Honzak, L.; Jiménez-Guerrero, P.; et al.
Abstract: The calculation of aerosol optical properties from aerosol mass is a process subject to uncertainty related to necessary assumptions on the treatment of the chemical species mixing state, density, refractive index, and hygroscopic growth. In the framework of the AQMEII-2 model intercomparison, we used the bulk mass profiles of aerosol chemical species sampled over the locations of AERONET stations across Europe and North America to calculate the aerosol optical properties under a range of common assumptions for all models. Several simulations with parameters perturbed within a range of observed values are carried out for July 2010 and compared in order to infer the assumptions that have the largest impact on the calculated aerosol optical properties. We calculate that the most important factor of uncertainty is the assumption about the mixing state, for which we estimate an uncertainty of 30–35% on the simulated aerosol optical depth (AOD) and single scattering albedo (SSA). The choice of the core composition in the core–shell representation is of minor importance for calculation of AOD, while it is critical for the SSA. The uncertainty introduced by the choice of mixing state choice on the calculation of the asymmetry parameter is the order of 10%. Other factors of uncertainty tested here have a maximum average impact of 10% each on calculated AOD, and an impact of a few percent on SSA and g. It is thus recommended to focus further research on a more accurate representation of the aerosol mixing state in models, in order to have a less uncertain simulation of the related optical properties. Highlights: We calculate optical properties from several aerosol models using same assumptions. We test choices on mixing state, refractive index, density and hygroscopicity. The most sensitive parameter is the aerosol mixing state. The related uncertainty on calculated AOD and SSA is 30–35%.